A Classical Review on Metal Toxicity with special reference to Dhatu Varga (International Journal of Ayurveda and Pharma Research, 2024)
A drug or formulation produces adverse events if it is not processed properly and used as per the classical guidelines. Aim and Objectives: In this review article, an attempt was made to throw some light on origins of those adverse drug reactions and various measures taken in literature. Material and Method: All the classical literature in Rasagrantha, Sangraha grantha, textbook of Ayurveda and Rasashastra regarding toxicity effect of Dhatu varga have been reviewed for this work. Observation and Result: For safe use of Dhatu Bhasma, various classical parameters at every stage of preparation and use have been stated. Starting from Grahyagrayatwa of raw metals, Samanya Shodhana of all Dhatus, toxic effect of improper processing of Dhatu Bhasma, and specific Puta for each Dhatu have been mentioned. Also, the Amruti Karana process, Samanya and Vishesh Bhasma Pariksha (parameters) have been exclusively done for the safety of Dhatu Bhasma. In order to reduce the residual toxic effect of Bhasma specific Anupana for specific Bhasma along with Pathyapathya have been detailed by ancient seers. Apart from that in case if any untoward effect has been found then the remedial therapies have been specified. Conclusion: Rasaushadhi can cause adverse effect if not prepared as per the classical guidelines. Hence there needs to follow classical guidelines at each and every step of Bhasma preparation scrupulously to get standard quality of Bhasma.